Efektivitas Penggunaan Dana Desa Pada Peningkatan Kesejahteraan Ekonomi Masyarakat Dalam Perspektif Ekonomi Syariah Di Desa Rejoagung Jombang - Azam, Ilyas Nurul; Salamah Layliya (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Village funds are one of the most important aspects of a village to carry out government programs. This includes programs for the welfare of the people in their area. It is believed that the village government is better able to see the priorities of the community's needs compared to the district government, which actually has a wider and more complex scope of problems. The purpose of this study is to determine the use of village funds, the effectiveness of the use of village funds for the economic welfare of the community and the use of village funds in a sharia economic perspective. This research uses a type of field research with a qualitative descriptive research method, the methods used in this research are: observation, interviews, and documentation. To analyze the data, the authors use the analysis of the Miles and Huberman models with deductive thinking methods. Based on the results of this study, it can be concluded that the implementation of the 2021-2022 Village Funds is well distributed because the use of Village Funds in the field of development and community empowerment is almost balanced, which will later create prosperity, prosperity, independence for the community and widespread development for the village.